Quantifying Transboundary Plastic Pollution in Marine Protected Areas Across the Mediterranean Sea - Hatzonikolakis, Yannis; Giakoumi, Sylvaine; Raitsos, Dionysios E.; Tsiaras, Kostas; Kalaroni, Sofia; Triantaphyllidis, George; Triantafyllou, George (Frontiers in Marine Science, 2022)
Micro- and macro-plastics pollution is a growing threat for marine biodiversity, ecosystem functioning, and consequently human wellbeing. Numerical models that consider main sources of plastics and simulate their dispersal characteristics are unique tools for exploring plastic pollution in marine protected areas (MPAs). Here, we used a Lagrangian plastic drift model, taking into account various sizes/types of plastic litter, originating from major land-based sources (coastal cities and rivers), to predict plastic accumulation zones in protected areas of the Mediterranean Sea (i.e., nationally designated MPAs, Natura 2000 sites, and Cetacean Critical Habitats). The model predicted that the size of plastic litters plays a key role in their dispersion and ultimate destination (i.e., larger litter travel longer distances). Most of the studied Mediterranean countries (13 out of 15) had at least one national MPA with over 55% of macroplastics originating from sources beyond their borders. Consequently, in many cases, local efforts to reduce plastic pollution in protected areas would be insufficient, especially for macroplastics management. Transboundary collaboration among Mediterranean countries is critical for implementing successful management plans against plastic pollution in their territorial waters and specifically in MPAs.